The relationship between ignimbrite lithofacies and topography in a foothill setting formed on Miocene pyroclastics – a case study from the Bükkalja, Northern Hungary - Biró, Tamás; Hencz, Mátyás; Telbisz, Tamás; Cseri, Zoltán; KarátsonDávid (Hungarian Geographical Bulletin, 2022)
Units with extremely variable erodibility are typical in the succession of pyroclastic-dominated volcanic fields. Welded ignimbrites are usually resistant to erosion, thus, they often appear as positive landforms, i.e., mesas or tilted plateaus after millions of years of denudation. The Bükkalja Volcanic Area being part of the most extended foothill area of the North Hungarian Mountains, is composed predominantly of Miocene ignimbrites, where the frequency distributions of elevation a.s.l., slope, aspect, as well as topographic openness, were investigated using a 30 m resolution SRTM-based digital surface model at four sample areas located at different relative distances from the assumed source localities of the ignimbrites, showing both non-welded and welded facies. The degree of dissection was also examined along swath profiles. The topography of the sample area closest to the source localities is dominated by slabs of moderately dissected welded ignimbrites, gently dipping towards SE. Farther away from the source the topography is dominated by erosional valleys and ridges, resulting in a narrower typical elevation range, a higher proportion of pixels with greater than 5° slope, higher frequencies of NE and SW exposures, and more significant incision resulted in more frequent pixels with positive topographic openness less than 1.5 radians here. Higher thicknesses and emplacement temperatures of ignimbrites, often showing welded facies are more common closer to the source vent. Thus, the erosional pattern around calderas can be used to draw conclusions on the spatial extent of the most intense ignimbrite accumulation, i.e., the location of eruption centres even in highly eroded ignimbrite fields.